Pendidikan Politik Pemilih Muda Oleh Komisi Pemilihan Umum Kota Bandung Melalui Program Rumah Pintar Jelang Pemilihan Umum 2024 - Syakira Syafiqya Tsabita Putri Hartono; Yusa Djuyandi (Polsight, 2024)
Abstract Political education is a crucial process and is attached to the KPU, aimed at ensuring voters understand the essence of holding elections and their impact on democracy. One of the voter segments that plays a big role in elections in Indonesia is young voters. Political education for young voters in Bandung City in order to encourage political awareness and personality can be done in various ways, one of which is by using the Bandung City KPU Election Smart House (RPP). This research uses qualitative research methods with interviews as primary data sources, literature studies and documentation as secondary data sources. The interview technique used a purposive technique, informants came from the Bandung City KPU and young voters who had visited the Bandung City KPU RPP. The data analysis technique was carried out using the Miles and Huberman technique, namely the process of reduction, data presentation and verification. The data triangulation process in this research also uses data source triangulation. The results of the research show that political education through the Bandung City KPU RPP for young voters is carried out by physically procuring and also digitizing political materials. In actualization, the RPP also provides information according to the needs of young voters. The political education process through the Bandung City KPU RPP has had a significant impact on the understanding, awareness and political personality of young voters, especially in the 2024 simultaneous election agenda. Keywords: Political Education, Election Smart House, Young Voters, Bandung City KPU.